Lower leg overuse injuries in high school first team schoolgirl hockey players - M. Petrick; K. F. Laubscher; E. M. Peters (AOSIS, 1993)
Questionnaires eliciting training histories and injury profiles were sent to the first team female hockey players and coaches of the top seven hockey schools in the Griqualand West and Southern Transvaal high school leagues during the 1990 hockey season. During this season, 27,4% (n=43) of the players reported that they had experienced pain in the lower leg area. The findings of this study suggest that some degree of pes planus may be a common problem and that the wearing of hockey boots may reduce the risk of lower leg pain. A general lack of knowledge about lower leg overuse injuries and their prevention was apparent amongst the players. The need for education on these injuries and their prevention was identified and recommendations for closer liaison between coaches and players were made.